2020
DOI: 10.1136/archdischild-2019-317787
|View full text |Cite
|
Sign up to set email alerts
|

Biliary atresia screening in Shenzhen: implementation and achievements

Abstract: ObjectiveTo elaborate on the implementation and achievements of a biliary atresia (BA) screening programme in Shenzhen.MethodsIn 2015, we partnered with the government in Shenzhen and attached the stool colour card (SCC) to the health handbook for mothers and children. These handbooks have been distributed through official channels to every pregnant woman in Shenzhen since 1 January 2015. A total of 118 patients diagnosed with BA at Shenzhen Children’s Hospital were enrolled and divided into two cohorts based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…Included studies were retrospective cohort studies (n=4),12–15 prospective cohort studies (n=12),6 7 16–25 cross-sectional studies (n=7),26–32 case–control studies (n=2)33 34 and cost–benefit analyses (n=2) 35 36. Two studies were conducted in the USA,22 27 two in Canada,7 25 seven in China,13 15 20 28 29 31 32 six in Japan,16 17 19 26 30 33 six in Taiwan6 12 14 18 21 23 and two in the UK 24 34. Two studies were cost-effectiveness analyses and so had no designated nation 35 36.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Included studies were retrospective cohort studies (n=4),12–15 prospective cohort studies (n=12),6 7 16–25 cross-sectional studies (n=7),26–32 case–control studies (n=2)33 34 and cost–benefit analyses (n=2) 35 36. Two studies were conducted in the USA,22 27 two in Canada,7 25 seven in China,13 15 20 28 29 31 32 six in Japan,16 17 19 26 30 33 six in Taiwan6 12 14 18 21 23 and two in the UK 24 34. Two studies were cost-effectiveness analyses and so had no designated nation 35 36.…”
Section: Resultsmentioning
confidence: 99%
“…Data for the effect on screening on the resulting age of Kasai were available for eight studies: seven using SCC and one using conjugated bilirubin measurements (table 2). 6 12 13 17 18 21–23 33 All studies using SCC demonstrated a reduction in the age of Kasai, with the range of reduction being 8.4–25.0 days, and the average age at Kasai of 48.0–59.7 days after SCC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The stool color card as a screening test in China has helped to move up the diagnostic time of BA to the neonatal period (23). Early operation within two months of age helped to improve the overall prognosis (24).…”
Section: Discussionmentioning
confidence: 99%
“…National BA screening programs using an SCC have been introduced in Switzerland and Japan [36,49]. Small pilot studies with the SCC have been conducted in regions or municipalities in Brazil [50], Cairo, Egypt [51], Shenzen (China) [52], Northern Portugal [53], and Lower Saxony Germany [54]. However, to our knowledge, comprehensive feasibility and performance studies of the SCC in these locales have not yet been reported.…”
Section: Ba Screening Using a Stool Color Cardmentioning
confidence: 99%